The Pragmatic Characteristics of Speech Acts - Madaminova Muhabbat (International Journal on Integrated Education, 2026)
This article provides a scientific and theoretical analysis of the discursive features of language functions within pragmalinguistic research. It explores the communicative, expressive, and persuasive functions of linguistic units in the process of discourse. The role of the relationship between speech subjects in shaping pragmatic meaning is also examined. Furthermore, the study reflects on the significance of context, communicative situations, and speech strategies within the structure of discourse. The article concludes with findings on the role of pragmalinguistics in modern linguistics and its methodological potential in discourse analysis.